CONCERT KIT SET DESIGN FOR K-POP FANS - Eunike Devina Tadjab Soetrisno; Wyna Herdiana; Brian Kurniawan Jaya (Ide dan Dialog Desain Indonesia (Idealog), 2022)
The phenomenon of K-Pop is growing rapidly, especially among Indonesian teenagers. Fans have active and participatory culture to support idols. One of the most favorite activities is watching concerts, so they can express their fanaticism by using various attributes. Due to the various kinds of equipment, such as lightstick to power bank, fans cannot enjoy the concert. This can be proven from the experience of fans when watching concerts who have trouble carrying equipment. The purpose of this research is to design a product that can help K-Popers in carrying concert equipment in a practical, comfortable, and expressive way. Qualitative methods were carried out by interviewing K-Pop fans who have watched concerts. Quantitative methods were carried out by questionnaires to know the designs that fans liked. From the research, known that bags, lightsticks, and cellphones are products that most often cause problems. So, the product set will consist a bag, lightstick handler, and grip along with a cellphone strap. Keywords : K-Pop fans, watching concert, expressive